(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The amorphous hydrogen bonded silicon atoms were introduced and their acceptor and donor sales properties formed in the silicon-locked zone were studied. In the atomi atomi in the atomi sifat, alsir er elements, and a new elements of the European elements, and the universal communication atomic, Erbus, Hydrogen, Golmy, Erbio, Hydrogan, Erbio, Hydrogan, Erbus, Hydrogeni, Erbi, Golitni, Erbus, Golitni, Erbekistan. Such a property of mixed European atoms has been found to be dependent on the formation of the 4f shell in it.